High-amylase corn hybrid in beef cattle diets and in high-moisture corn, and nutritive value of wet-milling corn by-products - de Souza Monteiro, Ludmila (My University, 2025)
A genetically modified corn hybrid with high [alpha]-amylase content was initially developed for the ethanol industry to reduce the need for adding exogenous amylase during fermentation. This hybrid has since gained attention in the animal industry as a promising feed source. The corn ethanol industry also produces by-products that serve as important feed resources for livestock, such as Sweet Bran (SB; Cargill, Blair, NE), a branded wet corn gluten feed. Two studies were done to evaluate the use of a high-amylase corn hybrid (Enogen corn; EC; Syngenta Seeds, LLC, Durham, NC) compared to a conventional corn (CON) as silage (SIL), steam-flaked corn (SFC), and high-moisture corn (HMC). A third study evaluated individual SB components in high-roughage diets. The first study aimed to evaluate growth performance of backgrounding steers as well as their subsequent finishing performance, carcass traits, and liver abscess incidence. Crossbred beef steers (n=912; 306 ± 8 kg initial body weight) were assigned to a randomized complete block design with four backgrounding treatments with two corn silage hybrids (EC-SIL or CON-SIL), and two SFC hybrids (EC-GRA or CON-GRA). During the finishing phase, animals were assigned to one of two grain hybrid treatments (EC-GRA or CON- GRA). There were no three-way interactions for measures of interest, and no differences among treatment combinations with respect to average daily gain (ADG) or incidence of abscessed livers (P > 0.10). During the backgrounding phase, steers fed EC-GRA had lower feed intake (P = 0.04) than CON-GRA, thus leading to improved overall gain:feed (G:F; P < 0.01). And during the finishing phase, overall G:F tended to be greater for cattle fed CON-GRA (P = 0.06). There was a tendency for interaction between GRA fed in the backgrounding and GRA fed in the finishing phase for hot carcass weight (HCW; P = 0.07), such that steers fed the same hybrid in both phases had greater HCW compared to those fed different hybrids in each phase. In the second experiment, fermentation characteristics, aerobic stability, and in vitro ruminal fermentation of HMC from either EC or CON, harvested at three distinct dry matter (DM) levels (66%, 71%, and 74.5%) and four storage lengths (30, 60, 90, or 120 d) were evaluated. In a randomized complete block design HMC was ensiled in 57 L plastic barrels. At d 30, EC 74.5% had the highest pH value (P = 0.07), followed by CON 74.5%. The lactic acid concentration was lowest for EC 74.5%, followed by CON at the same DM level, while the highest concentration was observed for EC 66%, which was similar to CON 66% (P < 0.0001). For yeast and mold count, CON 71% and 74.5% had higher amount at d 90 compared to other treatments, and all treatments by d 120, except EC 74.5%, lowered the count (P = 0.001). The DM was the only variable affecting aerobic stability (P < 0.0001), 66% was the most stable, and 74.5% was the least. Regarding the in vitro fermentation, 74.5% took longer to reach half of maximum gas production than 66% and 71% (P < 0.0001), and d 0 took longer than d 120 (P = 0.005). Control 66% had the highest rate of gas production, though not statistically different to EC 66% and 71% (P = 0.03). The objective of the third study was to evaluate digestibility, ruminal fermentation profiles, and feed intake behavior in steers fed high-forage diets containing individual components of SB. Twelve ruminally and duodenally fistulated Holstein steers (497 ± 19 kg) were assigned to one of four diets in a 4 x 4 Latin Square design. Diets included a control (CON; no SB components), solvent-extracted corn germ meal (Germ), corn bran (Bran), or corn steep liquor (Steep). Steers fed CON ate less than other treatments (P < 0.0001). Digestibility of protein of Steep diet was greater, for both ruminal and total tract digestion (P < 0.01). Additionally, Steep had higher total tract digestibility of starch (P = 0.03). Germ and Bran exhibited higher NDF digestibility than other treatments (P < 0.01), and CON had the lowest nutrients digestibility percentages. Diets with SB components decreased ruminal pH (P < 0.01) compared to CON. There were treatment differences (P < 0.01) in all feeding behavior variables. Steers on the Steep diet had the most frequent, shortest visits and the fastest intake rate, while CON steers had the fewest visits and slowest intake rate. Steers on Germ spent the longest total time eating. To conclude, type of grain fed in the backgrounding and finishing phases, but not silage, impacted overall system efficiency. In HMC, cultivar type showed minimal influence compared to DM content and storage length, yet the observed effect of EC on lactic acid concentration suggests potential for optimizing fermentation outcomes. Regarding SB, Steep contributed to greater digestibility percentages in our study, while Germ and Bran treatments were similar with respect to digestibility of most nutrients.
Keywords: Alpha-amylase; Backgrounding; Corn gluten feed; Finishing; High-moisture corn; Steam-flaked corn